Ameliorative effect of curcumin and vitamin B6 against lithocholic acid-induced cholestasis and liver injury in mice - Nassan, Mohamed A.; Ismail, Tamer A.; Soliman, Mohamed M.; Alkhedaide, Adel Q. (Brazilian Journal of Veterinary Pathology, 2018)
To examine the therapeutic effect of curcumin and/or vitamin B6 in treatment of cholestasis, a model of cholestasis was induced in mice using lithocholic acid (LCA). Alterations in biochemical parameters and liver histopathological and histochemical changes were examined in cholestatic mice and after treatments with curcumin, vitamin B6 and combination of both. Moreover, hepatic expressions of bilirubin-metabolizing enzymes, their regulatory nuclear receptors, and bile acid lipid transporters were examined using RT-PCR. Cholestatic mice showed an increase in the blood levels of AST, ALT, ALP, direct and total bilirubin and a decrease in cholesterol levels that were ameliorated by treatments. Liver histopathology showed multiple necrotic foci of different sizes spread all over the liver with congestion of hepatic blood vessels in LCA group. These foci were regenerated in hepatic tissues after administration of curcumin and vitamin B6. Immunohistochemical examination of liver showed an increase in glutathione and NF-kB expressions in treated mice. Cholestatic mice showed down-regulation of mRNA expression of hepatic bile acid and bilirubin-metabolizing/detoxifying enzymes (Cyp2b10, Ugt1a1, Sult2a1), their regulatory nuclear receptors (CAR, PXR, farnesoid X receptor), and bile acid/organic anion and lipid transporters (Oatp2, Bsep, Mrp2, Abcg8, Asbt). These changes were ameliorated and restored by treatment with curcumin, vitamin B6 and both. Only of examined genes, NTCP was up-regulated in cholestatic mice. In conclusion, treatment with curcumin mainly, vitamin B6 or the combination of them has the potential to ameliorate changes observed in induced cholestasis.